The mediation of power : a critical introduction - Davis, Aeron (London : Routledge, 2007)
'The Mediation of Power investigates how those in positions of power use and are influenced by media in their everyday activities. Each chapter examines this theme through an exploration of some of the key topic areas and debates in the field. The topics covered are: * theories of media and power * media policy and the economics of information * news production and journalistic practice * public relations and media management * culture and power * political communication and mediated politics * new and alternative media * interest group communications * media audiences and effects. In addition, the book presents a series of critical dialogues with the traditional paradigms in the field. These are rethought, supplemented or discarded altogether. The discussions are illustrated with original research material from a range of communication environments and case study examples. These document stock market crashes, E-democracy, the subcultures of the London Stock Exchange and Westminster Parliament, the strategies of corporate and political spin doctors, mass media influences on politicians and the Make Poverty History campaign. The debates are enlivened by first-hand accounts taken from over 200 high-profile interviews with politicians, journalists, public officials, spin doctors, campaigners and captains of industry. Tim Bell, David Blunkett, Iain Duncan Smith, Simon Heffer, David Hill, Simon Hughes, Trevor Kavanagh, Neil Kinnock, Peter Riddell, Polly Toynbee, Michael White and Ann Widdecombe are some of those cited.'
Includes bibliographical references (p. [187]-214) and index
Keywords: Mass media -- Political aspects; Mass media -- Political aspects -- United Kingdom; Communication in politics; Communication in politics -- United kingdom; Communication -- Political aspects; Communication -- Political aspects -- United Kingdom; Press and politics; Press and politics -- United Kingdom